Cockcroft–Swan Theorem for Projective Crossed Chain Complexes - Khmelnitskii, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
The Cockcroft–Swan theorem is proved for $n$-dimensional projective crossed chain complexes $(Pi,G, ∂_i)$, where $G = A * F$ is a free product of a fixed group $A$ by a free finitely generated group $F$.